Management of Intra-Aortic Balloon Pump Rupture and Entrapment - Bhamidipaty, Madhu (Aorta (Stamford), 2016)
While the intra-aortic balloon pump (IABP) itself has many useful and life-saving indications, it has a high complication rate, up to 30% in some studies. This report discusses the surgical removal and subsequent vascular repair in a patient with a ruptured and subsequently entrapped IABP and reviews the literature on the presentation and management of this rare but major complication.